2018
DOI: 10.1063/1.5045248
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric transmission based on magnetic resonance coupling in 3D-printed metamaterials

Abstract: The resonance based strong light-matter interaction in metamaterials offers unprecedented opportunities to manipulate polarization of electromagnetic waves. In this work, we fabricate a three-dimensional (3D) metamaterial consisting of 90-degreetwisted split-tube resonators using a 3D printing technique and demonstrate the corresponding asymmetric transmission for linearly polarized electromagnetic waves in the Ku band with near-unity polarization conversion efficiency. Experimental results reveal a 90-degree … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Regarding true 3D chiral metamaterials, the particles forming such structures are quite complicate objects (a true 3D chiral object is impossible to superimpose onto its mirror image even if it is lifted from its plane), so their fabrication poses a significant challenge. Fortunately, modern innovative technologies give amazing opportunities for production of true 3D chiral metamaterials, 26,27 and complex metamaterial systems with compensated chirality. 28 In particular, 3D-printing techniques allow producing structures with a complex spatial topology implementing meta-devices with a new functionality.…”
mentioning
confidence: 99%
“…Regarding true 3D chiral metamaterials, the particles forming such structures are quite complicate objects (a true 3D chiral object is impossible to superimpose onto its mirror image even if it is lifted from its plane), so their fabrication poses a significant challenge. Fortunately, modern innovative technologies give amazing opportunities for production of true 3D chiral metamaterials, 26,27 and complex metamaterial systems with compensated chirality. 28 In particular, 3D-printing techniques allow producing structures with a complex spatial topology implementing meta-devices with a new functionality.…”
mentioning
confidence: 99%
“…It is important to note that due to its unique structure, the optimal design in our study does not satisfy the transmission symmetry seen in the previously reported AT metamaterial based on twisted meta‐atoms, that is, t xx ≠ t yy , which can be clearly seen from the corresponding simulated transmittance spectra. [ 8,11,40 ] In other words, when the structure interacts with CP waves, AT is also expected. A signature of the twisted‐structure‐based AT metadevices is the relation between the AT (Δ) and the polarization angle, ϕ, that is, Δ x = (| t xy | 2 − | t yx | 2 ) cos 2ϕ.…”
Section: Resultsmentioning
confidence: 99%
“…To realize outstanding and tunable AT ef-fects in linearly and circularly polarized plane waves, several studies have been conducted, such as changing the shapes of symmetry-broken chiral metastructures, [21,22] increasing the layers of the proposed nanobars, [23,24] and tilting the rectangular nanoholes. [25] With regard to circularly polarized plane waves, high-efficiency broadband and dualband AT effects have been studied and realized from microwave to optical regimes, [20,[26][27][28] and tunable AT effects have also been realized by integrating the graphene layers with metamaterials. [29][30][31] With regard to linearly polarized plane waves, several studies have focused on enhancing the efficiency and broadening the band of the AT effect.…”
Section: Introductionmentioning
confidence: 99%